Análise de sistemas construtivos em madeira implantados na região de Curitiba - Paraná - Paese, Michelle Cristine Bonatto (2012)
The present study aims to conduct an assessment of building systems of wooden houses based in Light Wood Frame system, applied in Curitiba, Paraná. Interviews were conducted with companies that use system constructive Light Wood Frame in Brazil, more specifically in the region of Curitiba, Paraná. It was used a questionnaire with direct questions and open questions concerning production, material resources and production time. The conclusion was that the use of wood in housing construction technology is an appropriate solution and the system Light Wood Frame is a constructive alternative eco-efficient, because provides solutions to problems related to energy efficiency, sustainability and clean housing in Brazil. To a good performance in use of wood for houses to become a reality, the Brazilian production system needs to be submitted for standardization and regulations to increase the productivity of existing systems.